The Main Areas of Formation Telemedical Communication Systems of Republic Ecuador - SALEH, HADI M.; VELOZ, LLANO JUAN GABRIEL (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2018)
Health care market is one of the largest and fastest growing segments in developed countries. This article is devoted to the problem of creating a city segment of the infocommunication telemedicine system in the Republic of Ecuador, taking into account the importance of attenuation of radio waves due to territorial and climatic features in this territory.